Reflexiones sobre las raíces jurídicas Romanas del precedente “one ship company” / Think about the juridical Roman roots of precedent "one ship company" - Blázquez, Guillermo Suárez (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.169201 Trabalho enviado em 26 de abril de 2015. Aceito em 03 de maio de 2015. <p class="Paragraph SCX166733616" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Resumen <p class="Paragraph SCX166733616" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 47px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX166733616" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> El estudio pretende hacer un análisis histórico jurídico multidisciplinar de los antecedentes romanos que pueden haber influido, mediante su tradición en el derecho intermedio continental, en la configuración y formulación jurídica de los precedentes que configuran la estructura “One ship company” (vigente en el Common law de Inglaterra y en los países de su misma órbita jurídica). <p class="Paragraph SCX166733616" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX166733616" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Palabras claves: Transmarinas negotiationes, exercere navis, peculio, one ship company. Abstract With the present work we try to do a historical juridical multidisciplinary analysis of the Roman precedents that can have influenced, by means of his tradition in the intermediate continental law, in the configuration and juridical formulation of the precedents who form the structure " One ship company " (in force both in the Common law of England and in the countries of the same juridical system). Keywords: Transmarinas negotiationes, exercere navem, peculio, one ship company